2024
DOI: 10.1002/adfm.202309558
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Integration of Graphene and HfO2 Memristors

Urška Trstenjak,
Kalle Goß,
Alexander Gutsche
et al.

Abstract: The past decade has seen a growing trend toward utilizing (quasi) van der Waals growth for the heterogeneous integration of various materials for advanced electronics. In this work, pulsed‐laser deposition is used to grow HfO2 thin films on graphene/SiO2/Si. As graphene is easily damaged under standard oxide‐film deposition conditions, the process needs to be adjusted to minimize the oxidation and the collision‐induced damage. A systematic study is conducted in order to identify the crucial deposition paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This approach offers a solution to the degradation issues related to the CBRAM. In addition, 2D material-based memristors have a high potential for several applications owing to their high ON/OFF ratio, threshold switching characteristics with a low-compliance current, increased switching speed, ultralow power consumption (fJ per switching), and gigahertz operation. In terms of scalability, the atomic-scale thickness of 2D materials enables their applications in a variety of structures, such as three-dimensional (3D) vertical or lateral channels, thus presenting the possibility of increasing device density. Specifically, research using a 2D electrode edge contact selector has demonstrated the capability to reduce off currents, thus improving power consumption and highlighting the potential for advances in energy-efficient neuromorphic computing research. , Furthermore, recent 2D memristor studies suggest the emulation of various synaptic properties and their suitability for neuromorphic computing as well as structural improvements. Table lists the previous studies related to STM and LTM characteristics and synaptic properties of other 2D memristors. ,,, Here, we demonstrate the coexistence of STM and LTM properties in MoS 2 -based atomristors.…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers a solution to the degradation issues related to the CBRAM. In addition, 2D material-based memristors have a high potential for several applications owing to their high ON/OFF ratio, threshold switching characteristics with a low-compliance current, increased switching speed, ultralow power consumption (fJ per switching), and gigahertz operation. In terms of scalability, the atomic-scale thickness of 2D materials enables their applications in a variety of structures, such as three-dimensional (3D) vertical or lateral channels, thus presenting the possibility of increasing device density. Specifically, research using a 2D electrode edge contact selector has demonstrated the capability to reduce off currents, thus improving power consumption and highlighting the potential for advances in energy-efficient neuromorphic computing research. , Furthermore, recent 2D memristor studies suggest the emulation of various synaptic properties and their suitability for neuromorphic computing as well as structural improvements. Table lists the previous studies related to STM and LTM characteristics and synaptic properties of other 2D memristors. ,,, Here, we demonstrate the coexistence of STM and LTM properties in MoS 2 -based atomristors.…”
Section: Introductionmentioning
confidence: 99%